1990
DOI: 10.1180/minmag.1990.054.375.15
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum migration in the Miocene Monterey Formation, California, USA: constraints from fluid-inclusion studies

Abstract: The Miocene Monterey Formation constitutes a fracture-controlled petroleum reservoir, with intercalated calcareous and fine-grained siliceous rocks serving as both the source and reservoir for oil accumulations. Petroleum is produced from macroscopic fractures, and numerous tar and asphalt seeps at the surface attest to the present-day movement of hydrocarbons through fractures in the Monterey Formation. Many fractures are filled with carbonate (mostly calcite and dolomite), quartz, baryte and anhydrite. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…Studies have shown that oil inclusions of higher API gravity and maturity fluoresce in the blue end of the visible spectrum, whereas those of lower API gravity and maturity fluoresce in the red region (McLimans, 1987;Bodnar, 1990). Largely the relationship is based on observations made concerning the fluorescence properties of crude oils (Downare and Mullins, 1995;Ralston et al, 1996).…”
Section: Oil Inclusion Fluorescencementioning
confidence: 94%
“…Studies have shown that oil inclusions of higher API gravity and maturity fluoresce in the blue end of the visible spectrum, whereas those of lower API gravity and maturity fluoresce in the red region (McLimans, 1987;Bodnar, 1990). Largely the relationship is based on observations made concerning the fluorescence properties of crude oils (Downare and Mullins, 1995;Ralston et al, 1996).…”
Section: Oil Inclusion Fluorescencementioning
confidence: 94%
“…It can be concluded that the secondary organic inclusions are the record of secondary migration of the oil generated from Es4 . The abundance of the organic inclusions reflects the migration direction of oil or gas ( Bodnar, 1990) . The contents of organic inclusions in Es3 are much higher than those of Es4, also suggesting that the migration direction of oil and gas be from Es4 to Es3.…”
Section: Discussionmentioning
confidence: 99%
“…The eutectic tem per a tures sug gest the NaCl-CaCl 2 -MgCl 2 -H 2 O system, while the ice melt ing tem per a ture in di cates fluid sa lin ity of 13.52 wt.% NaCl eq. (Brown, 1982;Burruss, 1987;Bodnar, 1990;JarmoÂłowicz-Szulc et al, 2011). In the east ern part of the study area, the microthermometric re sults of one-phase in clusions (Skhidne Dovhe 3, Lanivka 1) sug gest sa lini ties of 9 wt.% NaCl eq., den si ties of ~1.1 g/cm 3 trap ping con di tions <60°C and pres sures of about 375 bars (see JarmoÂłowicz-Szulc et al, 2011).…”
Section: Diagenetic Conditions Of Carbonate Cementationmentioning
confidence: 99%